THE INFLUENCE OF JOB STRESS ON TEACHER PERFORMANCE AT STATE 2 NUNUKAN HIGH SCHOOL NUNUKAN DISTRICT, NORTH KALIMANTAN PROVINCE - Khusnul Fatimah; Dg. Maklassa; Andi Risfan Rizaldi (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine the effect of work stress on teacher performance at Nunukan 2 State High School, Nunukan Regency, North Kalimantan Province. The population in this study was all civil servant teachers and honorary teachers at State High School 2 Nunukan totaling 32 people. The type of research used is descriptive quantitative, the data sources used are primary and secondary data where the primary data comes from observations and questionnaires. Meanwhile, secondary data is obtained from documentation. The data analysis technique used is Simple Regression Analysis using statistical calculations via the Statistical Package for the Social Science (SPSS) version 27 application.The results of the research show that Job Stress (X) has a positive and significant influence on Teacher Performance (Y) seen from the results of the tcount > ttable (6.332 > 1,694) and the significant value = 0.00 < 0.05.